2020
DOI: 10.1029/2019jb018893
|View full text |Cite
|
Sign up to set email alerts
|

Stable Rate of Slip Along the Karakax Section of the Altyn Tagh Fault from Observation of Interglacial and Postglacial Offset Morphology and Surface Dating

Abstract: Digital elevation maps obtained using TanDEM‐X and Pleiades data combined with newly obtained surface age estimates using cosmogenic radionuclide (CRN) and optically simulated luminescence (OSL) methods are used to quantify the slip rate along the western section of the Altyn Tagh Fault in southern Xinjiang. The reconstruction of the conical shape of massive alluvial fans inferred to be from the Eemian (115±7 ka) from CRN dating shows consistent left‐lateral offsets of 300±20 m, yielding a slip rate of 2.6±0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 57 publications
10
18
0
Order By: Relevance
“…Lastly, it should be noted that the offset of the T3′/T3 riser at Taersa (∼255 ± 10 m) is commensurate with that of the corresponding Eemian T4 fan reconstruction (300 ± 20 m) at Site 4 in Peltzer et al. (2020) located 18 km to the east (Figure 1b).…”
Section: Morphology Extent and Offsets Of The Taersa Fans/terracessupporting
confidence: 62%
See 1 more Smart Citation
“…Lastly, it should be noted that the offset of the T3′/T3 riser at Taersa (∼255 ± 10 m) is commensurate with that of the corresponding Eemian T4 fan reconstruction (300 ± 20 m) at Site 4 in Peltzer et al. (2020) located 18 km to the east (Figure 1b).…”
Section: Morphology Extent and Offsets Of The Taersa Fans/terracessupporting
confidence: 62%
“…This was also consistent with a convergence rate between India and Asia formerly estimated to be as large as ∼5 cm/yr based on Nuvel 1 and plate tectonic reconstructions (DeMets et al., 1990). Later on, quantitative field measurements and sampling suggested a slip rate bracket of 12–25 mm/yr in the last ∼115 ka (Ryerson et al., 1999; dataset published in Peltzer et al., 2020). Much slower slip rates, however, have been proposed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to avoid the ambiguity in correlating terrace surface ages with their upper or lower risers, the offset of the terrace itself may be determined (e.g., Lensen, 1964;Peltzer et al, 1988Peltzer et al, , 2020. In general, this is possible when the terraces bear particular syndepositional geomorphic markers at their surface (channels, ridges) or if the terraces have specific inherited shapes (fan shapes, slopes) that enables unambiguous geometric reconstructions.…”
Section: Reducing Uncertainty In Slip Rate Estimate From Terrace Riser Offsetsmentioning
confidence: 99%
“…A geologic deformation model may be produced in conjunction with geodetic deformation models, which are based primarily on GPS data. In the Uniform California Earthquake Rupture Forecast, version 3 (UCERF3), four deformation models were implemented with varying usage of geologic input data (Parsons et al, 2013), which incorporated per-earthquake uncertainty of long-term geologic slip rates. Additionally, two geodetic-based deformation models were implemented across the western U.S. in the U.S. National Seismic Hazard Model (NSHM) of 2014 (Petersen et al, 2015).…”
Section: Implications For Hazard Analysismentioning
confidence: 99%
“…Due to the time scales over which they average, geologic slip rates necessarily integrate multiple earthquake cycles into a single rate value. Geologic slip rates have been interpreted as constant over millennial time scales (e.g., Chevalier et al, 2012;Gold & Cowgill, 2011;Hubert-Ferrari et al, 2002;Noriega et al, 2006;Peltzer et al, 2020;Salisbury et al, 2018;Weldon & Sieh, 1985) but have also been shown to vary over centennial to millennial time scales across faults of various kinematics and strain rates (e.g., Burgette et al, 2020;Dolan et al, 2007;Friedrich et al, 2003;Gold & Cowgill, 2011;Gold et al, 2017;Hatem et al, 2020;Khajavi et al, 2018;Ninis et al, 2013;Onderdonk et al, 2015;Sharp, 1981;Wallace, 1987;Weldon et al, 2004;Zinke et al, 2017Zinke et al, , 2019. While observations of temporally variable geologic slip rates provide additional nuance into fault behavior from a tectonics standpoint (e.g., long-term record of earthquake clusters and lulls), their implementation in seismic hazard modeling remains challenging.…”
mentioning
confidence: 99%